MP-ASI Biscuits Formula of Hotong Buru (Setaria italica) Flour and Moringa Leaves (Moringa oleifera) as an Alternative Functional Food Product to Prevent Stunting - Siahaya, Griennasty Clawdya; Kakisina, Ferdi H.; Rehena, Zasendy; Pentury, Melkhianus Hendrik; Ivakdalam, Lydia M.; Leunupun, Trixie (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study aims to determine the effect of hotong buru flour formulation with moringa leaf flour on the nutritional content and antioxidant activity of complementary feeding biscuits. Research Methods: Pure experimental research with a research design using a Completely Randomized Design (CRD) consisting of 4 formulas with 3 replications. Where the results of the study showed that there was an effect of substitution of MP-ASI biscuits on the carbohydrate, protein and fat content of MP-ASI biscuits with a significant value of 0.006 <Î± 0.05 and there was no effect of substitution of MP-ASI biscuits on the water content with a significant value of 0.072> Î± 0.05 and ash content with a significant value of 0.103> Î± 0.05 and antioxidant content with IC50 values for concentrations of 0% (199: Weak), 25% (55.5: Strong), 50% (22.5: Very Strong), 75% (17.8: Very Strong). This study was conducted for 1 year with the target outputs being MP-ASI Biscuit Products with Hotong Kelor Formulation, and publication of National Journal articles.